Endourological management of multiple large bladder calculi over eroded mesh in an adult with augmented bladder and catheterisable continent appendicovesicostomy - Bitran, Joshua Nissim (BMJ Case Rep, 2021)
Migration of abdominal wall mesh in an augmented bladder is a rarely encountered complication leading to formation of bladder stones causing recurrent urinary tract symptoms. The usual management of this condition involves either open surgical or a percutaneous approach for removal of the stone and migrated portion of mesh. Diagnosis of a migrated mesh is usually made intraoperatively during cystolitholapaxy. Appropriate management results in symptomatic improvement. Endoscopic management through catheterisable continent appendicovesicostomy has not been described to manage this challenging condition. To the best of our knowledge, we describe herewith the first report of endoscopic management of a large bladder stone formed over migrated mesh which involved removal of migrated mesh with holmium laser via a Mitrafanoff.